Commémoration et écriture de l’histoire dans la grande presse allemande à l’époque de Guillaume II : 1789 – 1813 – 1848 - Philippe Alexandre (Recherches Germaniques)
Major anniversaries, such as the centennial of the French Revolution and the Battle of the Nations at Leipzig (October 16-19, 1813) as well as the fiftieth anniversary of the 1848 Revolution, were occasions for debates about the significance of these events or periods for European history, but also for the construction of a national narrative. In Wilhelmine Germany, these anniversaries were linked to particular political issues. For supporters of the order that had been in place since 1871, the aim was to give a teleological interpretation to national history since 1813 legitimizing not only the founding and constitution of the new empire but also the dynasty that held the imperial dignity. Opponents, however, wanted to restore the truth, that is, to correct the official historiography and to bring to light the dark sides of national history the regime was trying to suppress. By using these three anniversaries as examples, this study shows what contribution major German dailies made to the writing of history in the context of this culture of remembrance. Their discussion of German history can also be analyzed as a consequence of the vivid critical public opinion in imperial Germany, in a golden age of opinion press. This study will first show the variety of article genres that contributed to the debate; this attempt at a typology is followed by a content analysis that illustrates—following the scheme: causes, developments, consequences—how all the newspapers in the corpus used interpreted history according to an ideology and an editorial line. It is worth noting that this journalistic discussion focused essentially on three themes: Revolution, Constitution, and Fatherland. Underlying were major issues that touched on the specific situation in Wilhelmine Germany. The great collective merit of the daily press of the time was to offer contemporaries, but also future generations, a differentiated historiography and thus to encourage them to shape a critical conception of the national narrative, in between the theses of professional historians and the fables of school history textbooks.